The provision of fort-annexes on the Antonine Wall (Proceedings of the Society of Antiquaries of Scotland, 1995)
A paper suggesting that temporary bath houses were provided in the Wall forts until a planned vallum could be completed behind the Wall. Once the vallum plan was abandoned annexes were attached to each fort and the internal bath houses demolished to be replaced by larger bathing complexes.